3DPD: A photogrammetric pipeline for a PUSH frame stereo cameras. (April 2021) - Simioni, E.; Re, C.; Mudric, T.; Cremonese, G.; Tulyakov, S.; Petrella, A.; Pommerol, A.; Thomas, N.
Abstract: An innovative photogrammetric pipeline has been developed by INAF-Padova for the processing of the stereo images from the CaSSIS (Colour and Stereo Imaging System) (Thomas et al., 2014). CaSSIS is the multispectral stereo push frame camera on board ExoMars TGO (Trace Gas Orbiter) which will image 1.5% of the Mars surface in stereo mode with a spatial resolution of 4.6 ​m/pixel: the highest resolution single pass stereo capability currently operating at Mars. Data acquisition started in April 2018. The camera is able to provide two images of the same target from two different points of view along the same orbit and within one minute. The telescope is mounted on a rotational stage and its boresight is oriented to 10° with respect to nadir direction. After the acquisition of the first set of images looking forward along track, the rotational stage is rotated by 180° and a second set of images (looking backward) is acquired. The stereo pairs can then be processed to provide the 3D topography of specific targets. The suite of photogrammetry and imaging tools, named 3DPD (3Dimensional reconstruction of Planetary Data) (Simioni et al. 2017), is designed for processing stereo push frame data and producing the three-dimensional data for geomorphological analysis of planetary surfaces. The workflow involves a MATLAB tool for the preparation of the inputs (the mosaicked images and the projection matrices) to be ingested into the 3DPD matching core software. The pipeline is in continuous development and routinely ingests a large number of images that CaSSIS is presently acquiring and will continue to acquire in the future. CaSSIS 3DPD products are the unique DTMs available nowadays and the stereo products have been considered in some scientific work (as described in Section 6.2). The same pipeline faces the need of a dedicated pipeline for the Mercury Global Mapping with the Spectrometers and Imagers for the Mercury Planetary Orbiter (MPO) BepiColombo Integrated Observatory SYStem (SIMBIO-SYS) (Cremonese et al., 2020). Graphical abstract: Image 1 Highlights: 3-dimensional reconstruction software for planetary surfaces. High resolution DTMs of targets on the Mars surface provided by CaSSIS Stereo Camera images. Photogrammetric pipeline for push frame instruments from CaSSIS to Bepicolombo stereo camera STC/SIMBIOSYS. Archiving of the Digital Terrain Models obtained by the CaSSIS stereo pairs.